2008
DOI: 10.3201/eid1410.080236
|View full text |Cite
|
Sign up to set email alerts
|

Murine Typhus and Febrile Illness, Nepal

Abstract: Murine typhus was diagnosed by PCR in 50 (7%) of 756 adults with febrile illness seeking treatment at Patan Hospital in Kathmandu, Nepal. Of patients with murine typhus, 64% were women, 86% were residents of Kathmandu, and 90% were unwell during the winter. No characteristics clearly distinguished typhus patients from those with blood culture-positive enteric fever.I n 2001, we found Salmonella enterica serotype Typhi and S. enterica serotype Paratyphi A to be the most common causes of bloodstream infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
1
34
1
1
Order By: Relevance
“…Recently, relatively high rate of murine typhus was reported among febrile adults in Nepal [7], and serological studies performed in various countries outside the region highlight the importance of this disease in children [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, relatively high rate of murine typhus was reported among febrile adults in Nepal [7], and serological studies performed in various countries outside the region highlight the importance of this disease in children [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study done in Patan Hospital reported that no characteristics clearly distinguished typhus patients from those with blood culture-positive enteric fever 22 . A study done in Birendra hospital Kathmandu reported that Ofloxacin was most sensitive antibiotic in 95.23 % cases followed by third generation cephalosporins (Ceftriaxone and Cefixime) in 90.47 % cases.…”
Section: Resultsmentioning
confidence: 96%
“…In 10 large case series describing 841 patients with murine typhus, rash was found in 59%, but no localized inoculationtype lesions, similar to the one described here, were reported. [4][5][6][7][8][9][10][11][12][13] In a guinea pig model of R. typhi infection, intradermal inoculation of the organism resulted in cutaneous erythema, induration, and necrosis. 18 In another animal model, intended to predict eschar formation following infection with various rickettsial species, R. typhi failed to produce eschars in intradermally inoculated guinea pigs-a finding which the authors state is consistent with what is known clinically of typhus group rickettsioses in humans.…”
Section: Discussionmentioning
confidence: 99%
“…3 The disease presents as an undifferentiated febrile illness accompanied by a maculopapular rash in 59% of infected persons. [4][5][6][7][8][9][10][11][12][13] Unlike many spotted fever group rickettsioses (SFGR) and scrub typhus, infection caused by R. typhi is not associated with an inoculation lesion. We herein describe a patient with murine typhus and an unusual clinical feature at the site of rickettsial inoculation.…”
Section: Introductionmentioning
confidence: 99%